Correlation between the Management Factors Affecting PMO Implementation in UAE Construction - Saleh Almansoori, Maitha Taher; Abdul Rahman, Ismail; Hameed Memon, Aftab (International Journal of Sustainable Construction Engineering and Technology, 2021)
PMO is a very effective strategy for improving construction performance. In the UAE construction industry, PMO is a relatively new trend. Hence it is facing several challenges during construction project implementation. These challenges affect PMO performance. Thus, this study identified the major management-related issues and assessed the correlation between the identified factors better to understand PMO implementation performance in the UAE construction industry. The study adopted a quantitative approach where the data was collected using a designed questionnaire. It used simple random technique sampling and gathered 100 valid questionnaire forms against 200 distributed questionnaires forms. The reliability test shows that the data was excellent, having an Alpha value of more than 0.8. Based on the Spearman test, a correlation matrix was developed to understand the relationship between the factors. Based on the correlation matrix, it is found that â€œinexperienced PMO leadership and project managersâ€, â€œunskilled and inexperienced project management personnel,â€ and â€œinability to identify the required soft skills in the implementation of PMOâ€ are mutually correlated with each other. In the project management domain, important factors are â€œoverworked project managers due to additional administrativeâ€, â€œa poorly laid communication strategy on the implementation of PMO purposes and goalsâ€, â€œminimize bureaucracy to the existing organizational structureâ€ , â€œunacceptance from senior managementâ€ and â€œselection of the right system to be usedâ€ has a high correlation with the factor â€œInaccurate information for reportingâ€. The findings of this study will be helpful for decision making to prioritizing for mitigating or taking corrective actions.